The nucleotide sequence of the rat cytoplasmic beta-actin gene. - Nudel, U (1983)
The nucleotide sequence of the rat beta-actin gene was determined. The gene codes for a protein identical to the bovine beta-actin. It has a large intron in the 5' untranslated region 6 nucleotides upstream from the initiator ATG, and 4 introns in the coding region at codons specifying amino acids 41/42, 121/122, 267, and 327/328. Unlike the skeletal muscle actin gene and many other actin genes, the beta-actin gene lacks the codon for Cys between the initiator ATG and the codon for the N-terminal amino acid of the mature protein. The usage of synonymous codons in the beta-actin gene is nonrandom, and is similar to that in the rat skeletal muscle and other vertebrate actin genes, but differs from the codon usage in yeast and soybean actin genes.